Artificial Intelligence as a catalyst for the Sustainability of Small and Medium Scale Businesses (SMEs) in Nigeria - Ebuka, Arachie Augustine; Emmanuel, Dibua; Idigo, Peter (Annals of Management and Organization Research, 2023)
Purpose: This study examines the role of AI in small business operations. Specifically, we identified areas where AI could be deployed, barriers to deployment of AI, identified AI tools in business, and ascertained the number of SMEs that consciously use any form of AI in their business operations. Research Methodology: This study adopted a descriptive design. The population of the study was 27546 small businesses that were registered under the Cooperate Affairs Commission (CAC), and a sample size of 379 was arrived at by adopting Krejcie and Morgan's 1970 sample size determination formula. The source of data was solely primary through interviews, which later formed a stepping stone for the structured questionnaire used for the study. The instrument was validated and tested for reliability. Data analysis was performed using descriptive statistics consisting of frequencies and percentages. Results: Most SMEs in Nigeria are still operating manually; hence, they do not enjoy the massive potential of AI deployment and remain perpetually small in size. Limitations: Descriptive statistics for the analysis were used to reduce the inferrability of the findings. Contribution: Given the increasing dependence on technology and AI, this study highlights the importance of AI not only for big and multinational corporations, but also for SMEs in Nigeria. Novelty: A study of this nature has not been undertaken in Nigeria, specifically focusing on southeast Nigeria, which has a large number of small businesses in the region.